Haere whakamua, hoki whakamuri, going forward, thinking back : tribal and hapū perspectives of the past in 19th century Taranaki : a thesis submitted for the degree of Doctor of Philosophy in History at Massey University - Keenan, Danny (Massey University, 1994)
This thesis advances a range of historical processes and frameworks through which tribes and hapū constructed their knowledge of the past. The thesis, in so doing, constructs an intellectual landscape upon which tribes and hapū assembled and managed that knowledge of the past. It focuses specifically on the nature of tribal and hapū history in Taranaki, though aspects of this study may apply to tribes and hapū in other parts of New Zealand. The thesis suggests ways in which tribes and hapū in Taranaki organised that knowledge of the past, and the reasons why. The thesis first suggests a distinction between tribal narratives and tribal histories. Tribal narratives provided accounts of the past in largely unmediated form. From these, tribes constructed tribal histories assembled for specific purposes. Such constructions were achieved through certain customary frameworks and processes. Whakapapa and mana are advanced as the two central factors influencing the shape and focus of these histories, whakapapa as primary organising device with mana serving as primary organising principle. This is illustrated by an examination of how various tribes of Taranaki constructed such mana histories comprising whakapapa selections of celestial descent (mana wairua), mortal forebears (mana tūpuna) and occupation of the land (mana whenua). Such histories were important because they validated tribes in the past and present. The thesis examines select tribes in Taranaki establishing their mana whenua presence on the land over time. Major landmarks of Te Atiawa whānui in the north especially illustrate how the sense of mana whenua was constructed over and attached to an ancestral landscape. After 1841, changes in the perceptions of landscape are noted following large-scale immigration. Some implications arising from such changed perceptions as they influenced new law and public policy are detailed. Thereafter, the study focuses on how the tribes sought to maintain and assert their mana whenua in the new environment based on the authority of their tribal histories as source of tribal mana. These validated continuing independence of activity commensurate with longstanding tribal precedence and practices, a source of authority that underpinned tribal activity from 1841 to at least 1900 (when this study concludes). Such frameworks of past knowledge continued to override new imperatives introduced into the Māori intellectual domain after 1841. The Māori past has normally been examined in a race-relations context. This thesis proposes an alternative theoretical basis for the examination of tribal and hapū history in the last century. An afterword considers the wider implications of this study for Māori and New Zealand historiography.
Keywords: New Zealand; Taranaki; History; Colonization; Māori (New Zealand people); Attitudes; Hapū; Iwi; Māori Doctoral Thesis